Nitrogen stress inhibits root growth by regulating cell wall and hormone changes in cotton (Gossypium hirsutum L.). (1st August 2021) - Chen, Jing; Wang, Zhanbiao; Liu, Shaodong; Zhang, Siping; Ge, Changwei; Shen, Qian; Ma, Huijuan; Zhang, Xiaomeng; Dong, Helin; Zhao, Xinhua; Liu, Ruihua; Pang, Chaoyou
Abstract: Roots play an important role in the response to nitrogen stress in cotton. To better understand the molecular and physiological mechanisms underlying the adaptation of cotton roots to nitrogen stress, the responses of genes in roots to nitrogen changes were analysed by RNA sequencing (RNA‐seq), and morphological and physiological indicators were measured for verification. This study revealed that lack of nitrogen stress (LN, 0 mm ) and excess nitrogen stress (HN, 8 mm ) inhibited root growth. Moderate nitrogen (MN, 4 mm ) resulted in the largest values for root length, projected area and volume. Nitrogen stress regulated root growth via two mechanisms. Nitrogen stress decreased root growth by regulating cell wall growth via alterations in the cell wall composition and the expression of cell wall‐related genes. Under LN and HN, the contents of cellular polysaccharide and glucan reached their lowest levels, whereas the contents of lignin and cellulose reached their highest levels. Lower expression of EXPA17, EXLB1 and PME3 as well as higher expression of EXLA1, WAT1, CESA1, CESA3, CAD6, COMT1, SAMS, LAC4 and NAC081 were obtained under nitrogen stress compared to MN, indicating that nitrogen stress increases lignin and cellulose synthesis and promotes root ageing. Nitrogen stress also decreased root growth by affecting the contents and regulation of salicylic acid (SA), jasmonic acid (JA) and abscisic acid (ABA). Nitrogen significantly upregulated the expression of PAD4, ALD1, WRKY70, WAKL10, MYB44, FER, LHY and BHLH112 as well as significantly downregulated that of TGA6, BT1, BT2 and PYL4. The changes in the expression of these genes under nitrogen stress resulted in significant increases in the SA, JA and ABA contents in roots. Our results suggested that nitrogen stress inhibits the growth of the cotton root system by affecting cell wall growth and hormone regulation. These results contribute to our understanding of how nitrogen regulates cotton root growth at the genetic and physiological levels, and they provide a theoretical basis for the efficient utilization of nitrogen resources.